Designing urban futures: a methodological framework for the spatial allocation of nature-based solutions through participatory planning and ecosystem services evaluation (2025)
Cities in the Global South, particularly in Latin America and the Caribbean are increasingly vulnerable to the compounded effects of climate change, unplanned urban expansion, and persistent socio-environmental inequalities. Rapid urbanization in these regions often occurs in contexts marked by institutional fragility, weak land governance, and limited technical or financial resources. As a result, Nature-based Solutions (NbS) have gained traction as cost-effective and multifunctional strategies for promoting climate resilience and sustainable urban development. However, the effective implementation of NbS remains constrained by key challenges: the lack of participatory planning frameworks, difficulties in selecting appropriate biophysical evaluation methods under data scarcity, and the limited use of economic valuation approaches to support informed decision-making. This thesis addresses key knowledge and implementation gaps by developing and testing a methodological framework tailored to the realities of resource-constrained urban environments in the Global South. The framework comprises a feasibility assessment, a Decision Support Tool (DST), and the application of economic valuation methods. Grounded in empirical research conducted in Bogotá, Colombia—within the urban renewal project El Reencuentro—the thesis explores three core dimensions of NbS planning: (i) the integration of socio-economic perceptions and stakeholder participation to define spatial priorities and select appropriate NbS typologies; (ii) the development of a DST to guide the selection of biophysical assessment methods under local constraints (e.g., limited data, budget, and technical capacity); and (iii) the application and comparative analysis of three economic valuation approaches (data synthesis, behavior-based, and stated-preference methods) to assess NbS benefits in data-scarce contexts. Each phase developed in this thesis follows a flexible, scalable, and context-sensitive structure, allowing their application at multiple urban scales (neighborhood, block, district) and under varying resource conditions. The methodology is based on a participatory framework for NbS location and selection, a biophysical evaluation tool for method selection, and a benefit economic valuation. The participatory framework incorporates citizens' preferences and socio-demographic factors to improve the social legitimacy and long-term relevance of NbS interventions. The biophysical evaluation tool introduces decision rules based on a systematic literature review of 256 studies, guiding the selection of feasible methods while avoiding overreliance on complex models in data-poor settings. The economic valuation analysis reveals the strengths and limitations of each method, underscoring the importance of climate awareness, education, and local knowledge in determining willingness to pay for ecosystem services. At a broader level, the thesis contributes to the growing call for inclusive, adaptable, and evidence-based planning approaches in the Global South. It demonstrates that simplified yet robust tools—grounded in participatory processes and aligned with local constraints—can enable cities to move beyond generic frameworks, transforming them into active agents of ecological restoration and social equity in the face of climate uncertainty.